Рецепция статуса украинского языка в российском языкознании: миф и реальность - Anatoljevna Kosmeda, Tatjana (Slavia Centralis, 2020)
The research of some of the modern Russian linguists (e.g. A. Kachmantova, N. Nikolina) promotes the idea of the non-existence of Ukrainian as one of the languages belonging to the group of East Slavic languages. These scholars believe that the group of East Slavic languages is composed of only the Russian language and its four variants: Greater Russian (main dialects: northern Russian, southern Russian and western Russian), Belarusian (main dialects: north-eastern, southwestern, Polessky), Red Russian (main dialects: Galician, Carpathian, Bukovyna), as well as the so-called Smaller Russian variant with its three main dialects – the Middle Dnieper, Slobozhany and Steppe. This suggestion implies that the Ukrainian language, similar to Belarusian, does not hold the status of an independent language, which is not true.
Keywords: Slavic languages in the East Slavic group; dialect; variant; status of the Ukrainian language